Validating a HACCP System for the Production of Vegetable Shito - Nina Bernice Ackah; Elvis Alfred Baidoo; Alexander Henry Kwadwo Appiah (Journal of Food Quality)
Vegetable shito is a novel pepper sauce product developed to cater for the needs of vegetarians. Due to its increasing popularity, it is prudent to assure its safety through the implementation of a quality management system for its production. This work was aimed at developing and validating a HACCP system for the production of vegetable shito. The HACCP system was successfully developed and validated to ensure that critical limits established for the critical control points were adequate to eliminate identified hazards. Validation was done through microbial challenge testing, and results obtained indicated that the HACCP plan developed will be effective in controlling and eliminating microbial hazards related to the vegetable shito. With such a quality management system in place, vegetable shito producers would be able to produce shito products which are safe and have a stable shelf life.